In vitro Regeneration of Wedelia calendulacea Less. - A Valuable Endangered Medicinal Plant (Plant Tissue Culture and Biotechnology, 2020)
Direct plant regeneration from shoot tips and nodal explants of Wedelia calendulacea Less. was carried out in MS with different concentrations and combinations of BAP, Kn and NAA. Of the two explants nodal segments showed the best response towards the formation of multiple shoots in MS containing BAP (2.0 mg/l), Kn (1.0 mg/l) and NAA (0.5 mg/l). In this combination, the maximum number of shoots/explant obtained was 18.33 ± 0.72 from shoot tips and 26.64 ± 0.47 from nodal explants. Cent per cent root formation was obtained in MS with IBA (0.2 mg/l) within three weeks. The in vitro regenerated plantlets were successfully transplanted to soil for further growth and development.Plant Tissue Cult. & Biotech. 30(2): 277-283, 2020 (December)